Hepatitis C Virus (HCV) clearance after treatment with direct-acting antivirals in human immunodeficiency virus (HIV)-HCV coinfection modulates systemic immune activation and HIV transcription on antiretroviral therapy - Ghiglione, Yanina Alexandra (2020)
Background. Hepatitis C virus (HCV) coinfection among people with human immunodeficiency virus (HIV) might perturb immune function and HIV persistence. We aimed to evaluate the impact of HCV clearance with direct-acting antivirals (DAAs) on immune activation and HIV persistence in HIV/HCV-coinfected individuals on antiretroviral therapy (ART). Methods. In a prospective observational study, ART-treated participants with HIV/HCV coinfection received sofosbuvir/ daclatasvir } ribavirin (n = 19). Blood samples were collected before DAA therapy, at the end of treatment, and 12 months after DAA termination (12MPT). T- and natural killer (NK)-cell phenotype, soluble plasma factors, cell-associated (CA)-HIV deoxyribonucleic acid (DNA) forms (total, integrated, 2LTR), CA-unspliced (US) and multiple-spliced ribonucleic acid (RNA), and plasma HIV RNA were evaluated. Results. Hepatitis C virus clearance was associated with (1) a downmodulation of activation and exhaustion markers in CD4+, CD8+ T, and NK cells together with (2) decreased plasma levels of Interferon gamma-induced protein 10 (IP10), interleukin-8 (IL- 8), soluble (s)CD163 and soluble intercellular adhesion molecule (sICAM). Cell-associated US HIV RNA was significantly higher at 12MPT compared to baseline, with no change in HIV DNA or plasma RNA. Conclusions. Elimination of HCV in HIV/HCV-coinfected individuals alters immune function and the transcriptional activity of latently infected cells. This report provides insights into the effects of HCV coinfection in HIV persistence and regards coinfected subjects as a population in which HIV remission might prove to be more challenging.